Nanocomposites Based on Self-Assembly Poly(Hydroxypropyl Methacrylate)-Block-Poly(N-Phenylmaleimide) and Fe3o4-Nps. Thermal Stability, Morphological Characterization and Optical Properties - Sanchez-Poblete, J (Elsevier B.V., 2018)
The current work presents the synthesis, characterization and preparation of organic–inorganic hybrid polymer films that contain inorganic magnetic nanoparticles (NPs). The block copolymer, prepared by Atom-Transfer Radical Polymerization (ATRP), was used as a nanoreactor for iron oxide NPs. The NPs were embedded in poly(hydroxypropyl methacrylate)-block-poly(N-phenylmaleimide) matrix. The following topographical modifications of the surface of the film were specially analyzed: control of pore features and changes in surface roughness. Finally, the NPs functionality inside the polymer matrix and how it may affect the thermal and optical properties of the films were assessed. © 2018 Elsevier B.V.